Doublecortin expression in the normal and epileptic adult human brain - Liu, Y. W. J.; Curtis, M. A.; Gibbons, H. M.; Mee, E. W.; Bergin, P. S.; Teoh, H. H.; Connor, B.; Dragunow, M.; Faull, R. L. M. (The European journal of neuroscience, 2008)
Mesial temporal lobe epilepsy (MTLE) is a neurological disorder associated with spontaneous recurrent complex partial seizures and hippocampal sclerosis. Although increased hippocampal neurogenesis has been reported in animal models of MTLE, increased neurogenesis has not been reported in the hippocampus of adult human MTLE cases. Here we showed that cells expressing doublecortin (Dcx), a microtubule‐associated protein expressed in migrating neuroblasts, were present in the hippocampus and temporal cortex of the normal and MTLE adult human brain. In particular, increased numbers of Dcx‐positive cells were observed in the epileptic compared with the normal temporal cortex. Importantly, 56% of Dcx‐expressing cells in the epileptic temporal cortex coexpressed both the proliferative cell marker, proliferating cell nuclear antigen and early neuronal marker, TuJ1, suggesting that they may be newly generated neurons. A subpopulation of Dcx‐positive cells in the epileptic temporal cortex also coexpressed the mature neuronal marker, NeuN, suggesting that epilepsy may promote the generation of new neurons in the temporal cortex. This study has identified, for the first time, a novel population of Dcx‐positive cells in the adult human temporal cortex that can be upregulated by epilepsy and thus, raises the possibility that these cells may have functional significance in the pathophysiology of epilepsy.